2002
DOI: 10.1128/jb.184.1.59-66.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Ralstonia eutropha PhaR Protein Couples Synthesis of the PhaP Phasin to the Presence of Polyhydroxybutyrate in Cells and Promotes Polyhydroxybutyrate Production

Abstract: Polyhydroxyalkanoates (PHAs) are polyoxoesters that are produced by many bacteria and that accumulate as intracellular granules. Phasins (PhaP) are proteins that accumulate during PHA synthesis, bind PHA granules, and promote further PHA synthesis. Interestingly, PhaP accumulation seems to be strictly dependent on PHA synthesis, which is catalyzed by the PhaC PHA synthase. Here we have tested the effect of the Ralstonia eutropha PhaR protein on the regulation of PhaP accumulation. R. eutropha strains with phaR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 27 publications
5
160
1
5
Order By: Relevance
“…Whereas P. oleovorans is estimated to have about one or two large granules (128). The PHA granules are mostly spherical and surrounded by a phospholipids membrane (129) separating two crystalline protein layers (130,131) composed of the PHA polymerases (132), the intracellular PHA depolymerase (133), amphipathic phasing proteins (117,134), PHAspecific regulator proteins (135)(136)(137) and additional proteins with unknown function ( Figure 5) (128). Granules membrane coat is about 2 nm thick, containing 0.5% lipid and 2% protein, of the granule weight (138).…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas P. oleovorans is estimated to have about one or two large granules (128). The PHA granules are mostly spherical and surrounded by a phospholipids membrane (129) separating two crystalline protein layers (130,131) composed of the PHA polymerases (132), the intracellular PHA depolymerase (133), amphipathic phasing proteins (117,134), PHAspecific regulator proteins (135)(136)(137) and additional proteins with unknown function ( Figure 5) (128). Granules membrane coat is about 2 nm thick, containing 0.5% lipid and 2% protein, of the granule weight (138).…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
“…Simulation of the selfassembly process showed that phasins might impact on the kinetics of granule formation by reducing the lag phase (147). Various PHA-specific regulators such as PhbR from C. necator (137,142). PhaF from Pseudomonads (135,148,149) and PhaR from Paracoccus denitrificans (136,150) were found to bind non-covalently to the PHA granules.…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
“…Phasins are the most abundant proteins in these intracellular inclusions, contributing up to 5% of the total cellular protein in bacteria (Steinbuchel et al, 1995;Wieczorek et al, 1995). In prokaryotes, phasin expression and lipid accumulation are tightly coupled and regulated by the cellular concentration of PhaR, a transcriptional repressor that can simultaneously bind to lipids and DNA elements (Maehara et al, 2002;Pötter et al, 2002;York et al, 2002;Yamada et al, 2007). Phasins stabilize lipid granules and prevent their fusion, a role that later in evolution is assumed by lipid droplet (LD)-associated proteins in eukaryotes.…”
Section: Lipid Accumulation As a Survival Strategy In Unicellular Orgmentioning
confidence: 99%
“…By looking at the entire proteome before and after changing specific environmental conditions, we identified an inducible promoter in R. eutropha that could be regulated with a simple process parameter (i.e., phosphate limitation). Previous work using shake flasks has shown that phaPp is induced under PHB production conditions and that expression is controlled by a DNA binding protein, PhaR (43).…”
Section: Discussionmentioning
confidence: 99%